Attachment Style Mediates the Relationship between Trauma and Somatic Distress among Individuals with Serious Mental Illness. Issue 2 (3rd April 2021) - Orme, William; Kapoor, Shweta; Frueh, B. Christopher; Allen, Jon G.; Fowler, J. Christopher; Madan, Alok
Abstract : Objective : Individuals with mental illnesses severe enough to require psychiatric hospitalization often have significant trauma histories, have developed maladaptive attachment styles, and experience comorbid somatic distress. Gaining an understanding about the interaction of such factors may lead to prioritizing interventions that target factors that mediate the relationship between trauma and adverse somatic distress. Prior research has examined various mediation models, but results have been mixed and conducted only on outpatient samples. Method : Participants (47.7% female) in a large sample ( N = 2702) with a mean age of 34.62 ( SD  = 14.7) were enrolled in a specialist inpatient program and completed self-report measures pertaining to demographics, attachment insecurity, lifetime trauma exposure, and somatic distress within 72 hours of admission. The dimensions of attachment insecurity (i.e., attachment anxiety and attachment avoidance) were tested as parallel mediators in the relationship between lifetime trauma exposure and somatic distress. Results : The mediation analyses revealed that attachment anxiety and avoidance partially mediated the relationship between lifetime trauma exposure and somatic distress. Conclusions : These results are the first to date to implicate both attachment anxiety and avoidance as mediators between trauma exposure and somatic distress in a high acuity sample. Although the results do not imply causality, they do call attention to social-cognitive factors related to somatic distress and highlight the importance of considering attachment styles as a possible contributor to comorbid physical symptoms in patients with trauma exposure.